2001
DOI: 10.1080/027868201300034844
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Cigarette Smoke Particles in the Human Respiratory Tract

Abstract: Understanding tobacco related cancer etiology requires the knowledge of cigarette smoke particle (CSP) deposition. Measurements of CSP deposition are inconsistent with typical deposition data. A deposition model that accounts for hygroscopic growth, coagulation, particle charge, and cloud behavior of CSP has not yet been presented. Nor have smoking patterns been accounted for in either deposition measurements or computer models. The dosimetry of Benzo[a]pyrene (BaP), which would add critical information to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 40 publications
2
78
2
1
Order By: Relevance
“…One important aspect to consider is the physical properties of inhalable aerosols and the representative parameter obtained from measured size distributions. Depending on the size distribution of an aerosol, some of the inhaled dose is transported further to the tracheobronchial section or to the alveolar region of the ''lung'' (Bernstein, 2004;Kane et al, 2010;Robinson & Yu, 2001). Generally, a respirable aerosol (Hinds, 2012) has a related mass median aerodynamic diameter (MMAD) of less than 2.5 mm; at this size, more than 80% of the aerosol mass reaches the alveolar region.…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect to consider is the physical properties of inhalable aerosols and the representative parameter obtained from measured size distributions. Depending on the size distribution of an aerosol, some of the inhaled dose is transported further to the tracheobronchial section or to the alveolar region of the ''lung'' (Bernstein, 2004;Kane et al, 2010;Robinson & Yu, 2001). Generally, a respirable aerosol (Hinds, 2012) has a related mass median aerodynamic diameter (MMAD) of less than 2.5 mm; at this size, more than 80% of the aerosol mass reaches the alveolar region.…”
Section: Introductionmentioning
confidence: 99%
“…Most mathematical particle deposition models will consider the first three of these mechanisms, which are generally the dominant ones, and sophisticated models may include additional mechanisms. (31)(32)(33)(34)(35)(36) Several reference books provide pertinent basic information on properties of aerosol particles and their behavior. (37)(38)(39)(40) Traditional particle deposition models apply particle deposition mechanisms to simplified airway structures to predict deposition doses for the major regions of the respiratory tract.…”
Section: Inhaled Aerosol Despositionmentioning
confidence: 99%
“…These authors provide little guidance as to when cloud settling will occur beyond stating that when the ratio is much greater than unity cloud settling occurs and when it is much less than unity it does not. Stober et al (1978), Chen and Yeh (1990), Martonen (1992), Phalen et al (1994), and Robinson and Yu (2001) observed bulk motion of mainstream cigarette smoke in air. Martonen (1992) observed the path of mainstream smoke in human airway casts and concluded from theoretical analysis that cloud motion would occur when a 3 mm diameter cloud has a mass concentration much >52 mg/m 3 .…”
Section: Introductionmentioning
confidence: 99%